CLONING AND IN SILICO STUDIES OF LIPASE GENE OF A THERMOPHILIC BACTERIA ISOLATED FROM THE HYDROTHERMAL VENT AREA OF KAWIO, NORTH - Lambangsari, Khalilan
Indonesia is an archipelago with a multi-faceted landscape and has an enormous biodiversity. Underwater volcanoes is an example of a natural habitat of thermophilic bacteria, such as the hydrothermal vent in Kawio, North Sulawesi. Opportunities for the discovery of new isolates of thermophilic microorganisms is enormous, considering that the conditions of the hydrothermal vent in Kawio are extreme and isolated. Previous studies had isolated several bacterial isolates from that area. The focus of this research was to screen these bacterial isolates for the production of thermostable lipase. In this study, the lipase gene from the selected isolate was cloned, seuquenced and in silico analysis was performed to predict the characteristics of the lipase protein. Based on the potential to produce lipase in growth media containing olive oil and rhodamine B as an indicator, one of three isolates screened showed an orange luminescence as the result of a positive reaction for the formation of rhodamine B and fatty acids complex. Phylogenetic analysis of 16S rRNA gene showed that the isolate was closely related to Bacillus safensis strain FO-26b with 96,87% homology. The results of the bacterial identification were then used as the basis for designing primers that would be used to isolate the lipase gene by Polymerase Chain Reaction. The lipase gene had been isolated and then ligated to the cloning vector pJET1.2/blunt to form the recombinant plasmid pJET-lip. This recombinant plasmid was used to transform Escherichia coli DH5?. After validation of the accuracy of lipase gene sequence, the lipase gene was analyzed and its structure determined in order to obtain information regarding the characteristics of lipase. Amino acids sequence analysis of the lipase showed similarity between lipase of Bacillus pumilus strain B106 with 98% homology. Further analysis at the protein level indicated that the lipase isolated from marine water was a member of family I.4 of 'true lipase' group. Phylogenetic analysis indicated that the isolated lipase gene was orthologous with lipase from Bacillus pumilus and Bacillus subtilis.